2011
DOI: 10.1523/jneurosci.2604-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Spindles in Humans: Insights from Intracranial EEG and Unit Recordings

Abstract: Sleep spindles are an electroencephalographic (EEG) hallmark of non-rapid eye movement (NREM) sleep and are believed to mediate many sleep-related functions, from memory consolidation to cortical development. Spindles differ in location, frequency, and association with slow waves, but whether this heterogeneity may reflect different physiological processes and potentially serve different functional roles remains unclear. Here we utilized a unique opportunity to record intracranial depth EEG and single-unit act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

81
487
6
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 456 publications
(577 citation statements)
references
References 93 publications
(149 reference statements)
81
487
6
3
Order By: Relevance
“…Instead, the results are more in line with recent findings in mammals suggesting that sleep may not be as global as previously thought. For example, intracranial recordings in epileptic patients have shown that the slow waves and spindles of NREM sleep often occur in some cortical areas but not in others (54) and frequently involve only small groups of neurons (55,56), a finding that was confirmed in rats (15). Recordings of evoked responses in the rat barrel cortex after whisker stimulation also suggest the possible occurrence of "local wake during sleep": responses sometimes appear sleeplike in one cortical column but wake-like in another (57).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the results are more in line with recent findings in mammals suggesting that sleep may not be as global as previously thought. For example, intracranial recordings in epileptic patients have shown that the slow waves and spindles of NREM sleep often occur in some cortical areas but not in others (54) and frequently involve only small groups of neurons (55,56), a finding that was confirmed in rats (15). Recordings of evoked responses in the rat barrel cortex after whisker stimulation also suggest the possible occurrence of "local wake during sleep": responses sometimes appear sleeplike in one cortical column but wake-like in another (57).…”
Section: Discussionmentioning
confidence: 99%
“…Early animal sleep spindle studies, using up to 8 electrodes in a linear array (Andersen et al, 1967;Kim et al, 1995;Contreras et al, , 1997, in addition to preliminary EEG evidence in the human (Achermann and BorbĂ©ly, 1998), proposed that spindles involve global synchronization of cortical circuits, raising the possibility that this sleep oscillation places neocortex into a specialized state for consolidation of long-term memories. In recent years, several studies have reported a mixture of 'local' and 'global' spindles using amplitude-duration thresholding approaches Andrillon et al, 2011). By carefully studying the phase information in the spindle frequency band recorded on large-scale ECoG arrays, we have uncovered that a substantial number of spindle oscillation cycles are organized into global, hemisphere-spanning patterns of rotating and expanding waves (Figure 1-figure supplement 7).…”
Section: Introductionmentioning
confidence: 89%
“…They further report that fast spindles often occur with slow-wave up-states and that spindle variability across regions may reflect the underlying TC projections. They do not find a consistent modulation of neuronal firing rates during spindles [47]. They also report that most sleep slow waves and spindles are predominantly local inferring therefore that the underlying active and inactive neuronal states also occur locally [48].…”
Section: Invasive Electrophysiologymentioning
confidence: 88%
“…An important recent study has provided valuable insights by characterizing sleep spindles in humans by pooling together simultaneous recordings of intracranial depth EEG and unit spiking activities in multiple brain regions in the hippocampus and cortex of 13 individuals undergoing presurgical localization of pharmacologically resistant epilepsy [47][48]. The authors of these studies report that spindles occur across multiple neocortical regions, and less frequently also in the parahippocampal gyrus and hippocampus.…”
Section: Invasive Electrophysiologymentioning
confidence: 99%